因式分解(m+n)(p+q)-(n-m)(p-q)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 01:22:50
因式分解(m+n)(p+q)-(n-m)(p-q)因式分解(m+n)(p+q)-(n-m)(p-q)因式分解(m+n)(p+q)-(n-m)(p-q)(m+n)(p+q)-(n-m)(p-q)=mp+
因式分解(m+n)(p+q)-(n-m)(p-q)
因式分解(m+n)(p+q)-(n-m)(p-q)
因式分解(m+n)(p+q)-(n-m)(p-q)
(m+n)(p+q)-(n-m)(p-q)
=mp+mq+np+nq-(np-nq-mp+mq)
=mp+mq+np+nq-np+nq+mp-mq
=mp+nq+nq+mp
=2mp+2nq
=2(mp+nq)
(m+n)(p+q)-(n-m)(p-q)
=mp+mq+np+nq-np+nq+mp-mq
=2mp+2nq
=2(mp+nq)
因式分解(m+n)(p+q)-(n-m)(p-q)
因式分解:(m-n)(p-q)-(n-m)^2(q-p)
因式分解 (m+n)(p+q)-(m+n)(p-q)
m(m-n)(p-q)-n(n-m)(p-q)因式分解
m(m-n)(p-q)-n(m-n)(q-p)因式分解
m(m-n)(p-q)-n(m-n)(q-p)的因式分解
(m+n)(p+q)-(m+n)(p-q)
(m+n+p-q)(m-n-p-q) 怎么算
计算 (p+q-m-n)(p-q-m+n)
(m+n)(p+q)-(m+n)(p-q)=
a(m-n)^p*(n-m)^q*(m-n)^q*(n-m)^p等于什么?
5m(p^2-q)^3-4n(q-p^2)^2因式分解
5m(p^2-q)-4n(q-p^2)^2因式分解
(m-n)(p-q)(p+2q)-(n-m)(p+q)(p+2q)
(m+n)(p-q)-(m+n)(q+p)
(m+n)(p-q)-(m+n)(p+q)
因式分解m(n-2)+p(2-n)-(2-n)^2
已知有理数m,n,p,q在数轴上的位置如图所示,且|m|=|n| ,化简(1)|m+n|+|m+p|+|q+p|(2)|n-m|--3|m+p|-|-n-q|+|q-p|